LITERASI KEWIRAUSAHAAN DAN KESIAPAN USAHA PEREMPUAN TANI DALAM PENGEMBANGAN PRODUK OLAHAN PALA BERNILAI EKONOMI - Irma Ibrahim; Sarmina Ati (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2026)
The utilization of nutmeg flesh as a value-added product remains limited, despite its significant potential to improve household income through product diversification. This study aims to analyze entrepreneurial literacy and business readiness among women farmers in developing value-added nutmeg products in Dorpedu Village, Ternate Island District, Ternate City, Indonesia. The study employed a mixed-methods approach with a case study design involving 11 women members of the Tubil Farmer Group. Data were collected through observations, semi-structured interviews, questionnaires, and documentation and were analyzed using descriptive statistics and thematic analysis. The findings indicate that entrepreneurship education and training improved participants' entrepreneurial literacy, particularly in identifying business opportunities, understanding value-added concepts, calculating production costs, determining selling prices, managing simple financial records, and utilizing social media as a marketing strategy. The improvement in entrepreneurial literacy also strengthened participants' business readiness to develop Nutmeg Balado Chips and Nutmeg Drink as local value-added products. These findings suggest that strengthening entrepreneurial literacy plays a crucial role in enhancing women farmers' business readiness and supports the sustainable development of local commodity-based enterprises.